Efek Imunologi pada Penggunaan Opioid Akut dan Kronis - Rahardjo, Sri; Widyastuti, Yunita; Rumpoko, Triaji Mudo (This journal is published by the Department of Anesthesiology and Intensive Therapy of Faculty of Medicine, Public Health and Nursing, in collaboration with the Indonesian Society of Anesthesiology and Intensive Therapy , Yogyakarta Special Region Br, 2020)
Opioids have become the flagship agents of modern perioperative care and pain management. The word opium comes from the Greek opion (“juice poppy”) or opium poppy (Papaver somniferum) is the source of 20 different alkaloids. Recent studies have shown that the role of opioid receptors on immune function is complicated, but they work through a variety of different mechanisms. Administration of various opioids shows different effects on the immune system: immunosuppressive, immunostimulatory, or both. Previously it was believed that most opioids suppress the immune system, but recent research suggests they may have a dual effect. However, the mechanism by which opioids and opioid receptors work in the immune system is still not clearly understood.